Ingestion of ‘whole cell’ or ‘split cell’ Chlorella sp., Arthrospira sp., and milk protein show divergent postprandial plasma amino acid responses with similar postprandial blood glucose control in humans - Williamson, Ellen; Monteyne, Alistair J.; Van der Heijden, Ino; Abdelrahman, Doaa R.; Murton, Andrew J.; Hankamer, Benjamin; Stephens, Francis B.; Wall, Benjamin T. (Frontiers in Nutrition, 2024)
Introduction Microalgae provide a sustainable basis for protein-rich food production. However, human data concerning microalgae ingestion, subsequent postprandial amino acid (AA) availability and associated metabolic responses are minimal. Objectives We investigated ingesting Arthrospira sp. (spirulina;SPR), and Chlorella sp. (chlorella; in ‘whole cell’ [WCC] and ‘split cell’ [SCC] forms, the latter proposed to improve digestibility), compared with a high-quality animal derived protein source (milk; MLK). Subjects/methods Ten participants (age; 21 ± 1y, BMI; 25 ± 1 kg·m−2) completed a randomised, crossover, double-blind study, partaking in 4 counterbalanced (for order) experimental visits. At each visit participants ingested SPR, WCC, SCC or MLK drinks containing 20 g protein and 75 g carbohydrate. Arterialised venous blood samples, indirect calorimetry and visual analogue scales were assessed postabsorptive, and throughout a 5 h postprandial period to measure AA, glucose, insulin and uric acid concentrations, whole-body energy expenditure and appetite scores, respectively. Results Protein ingestion increased plasma AA concentrations (p < 0.001) to differing total postprandial total—and essential—AA availabilities; highest for MLK (86.6 ± 17.8 mmol·L−1) and SPR (84.9 ± 12.5 mmol·L−1), lowest for WCC (−4.1 ± 21.7 mmol·L−1; p < 0.05), with SCC (55.7 ± 11.2 mmol·L−1) marginally greater than WCC (p = 0.09). No differences (p > 0.05) were detected between conditions for postprandial glucose or insulin concentrations, whole-body energy expenditure or appetite scores, but serum uric acid concentrations increased (p < 0.05) following microalgae ingestion only. Conclusion Our data imply that microalgae can present a bioavailable source of protein for human nutrition, however, challenges remain, requiring species selection and/or biomass processing to overcome.